Identification of a Ternary Nitride Ti10Cu3N4 with a Unique Structure Type - Hwang, Kyubin; Cho, Young Whan; Hong, Jihyun; Kim, Yunseok; Shim, Jae-Hyeok; Kim, Hyungsub; Lee, Young-Su (ACS Publications, 2024)
This study presents the synthesis and detailed structural analysis of the ternary nitride Ti10Cu3N4. Initially identified as Ti3CuN within the Ti-Cu-N ternary phase diagram, its crystal structure remained unresolved and was characterized solely as belonging to the tetragonal crystal system. Through a comprehensive structural analysis, this study proposes a revised stoichiometry as Ti10Cu3N4; its crystal structure represents a previously unreported structure type within the P4(2)/mnm space group. Its atomic arrangement was elucidated through a combination of X-ray powder diffraction profile analysis and density functional theory calculations, corroborated by neutron diffraction studies. Furthermore, the hydrogen storage properties of Ti10Cu3N4 were characterized, demonstrating a hydrogen absorption capacity of approximately 0.6 wt % with desorption occurring in the temperature range of 200-550 degrees C.